First degree friendship: cinematographic aspects of Franklin D. Roosevelt’s good neighbor policy towards Latin America - Lénárt, András (AMERICANA E-journal of American Studies in Hungary, 2018)
Cultural policy, including film policy, has played a crucial role in strengthening a country’s domestic and foreign policy. The United States of America’s attitude towards Latin America has been changed several times throughout the 20th century, depending on the current international situation. The aim of my article is to present the cinematographic aspects of this policy in the 1930s and the first half of the 1940s, within the framework of the Good Neighbor Policy, formulated by President Franklin Delano Roosevelt. In this mission special offices, departments and directors had a key role, with the support of several famous filmmakers.